Effect of physico-chemical characteristic of water in sub-critical condition towards structural conversion of mesocarp fiber - Mahandran, Sanggithapriya; Yoshida, Hiroyuki; Sabli, Nordin; Siajam, Shamsul Izhar (Centre for Environmental Sustainability and Water Security (IPASA), Universiti Teknologi Malaysia, 2019)
Water at subcritical state was studied as an alternative way to breakdown oil palm mesocarp fiber (OPMF). The complex structure of cellulose causes difficulty in breaking down the palm oil cell using physical industrial scale method. The decomposition of OPMF using subcritical water (Sub-CW) method has been carried out at reaction temperatures ranging from 200°C to 300°C with a constant reaction time of 5 minutes using batch stainless-steel tube as the reactor. The solid samples were viewed under SEM and found that surface of solid sample of 240oC is occupied by opened pores. The breakdown cell wall in form of monosaccharide contributes to increase in yield of total sugar from 5.81mg g-1 OPMF sample (200°C) to 22.17mg g-1 OPMF sample (240°C). However, yield of tar increase from 5.05mg g-1 OPMF sample (200°C) to 187.61 mg g-1 OPMF sample (300°C) due to pyrolysis process. Thus, particle size of OPMF after Sub CW reaction temperature elevated to 240°C to ease hydrolysis process and reduce as the sample degrade as temperature gets higher.